Impacts of mesoscale activity on the water masses and circulation in the Coral Sea. Issue 10 (3rd October 2016) - Rousselet, L.; Doglioli, A. M.; Maes, C.; Blanke, B.; Petrenko, A. A.
Abstract: The climatological vision of the circulation within the Coral Sea is today well established with the westward circulation of two main jets, the North Caledonian Jet (NCJ) and the North Vanuatu Jet (NVJ) as a consequence of the separation of the South Equatorial Current (SEC) on the islands of New Caledonia, Vanuatu, and Fiji. Each jet has its own dynamic and transports different water masses across the Coral Sea. The influence of mesoscale activity on mean flow and on water mass exchanges is not yet fully explored in this region of intense activity. Our study relies on the analysis of in situ, satellite, and numerical data. Indeed, we first use in situ data from the Bifurcation cruise and from an Argo float, jointly with satellite‐derived velocities, to study the eddy influence on the Coral Sea dynamics. We identify an anticyclonic eddy as participating in the transport of NVJ‐like water masses into the theoretical pathway of NCJ waters. This transfer from the NVJ to the NCJ is confirmed over the long term by a Lagrangian analysis. In particular, this numerical analysis shows that anticyclonic eddies can contribute up to 70–90% of the overall eddy transfer between those seemingly independent jets. Finally, transports calculated using S‐ADCP measurements (0–500 m) show an eddy‐induced sensitivity that can reach up to 15 Sv, i.e., the order of the transport of the jets. Key Points: Evaluation of the influence of mesoscale activity on in situ observations in the context of an oceanographic cruise Use of a Lagrangian analysis to validate a transport mechanism identified with in situ observations Identification of a new water mass pathway as a result of mesoscale eddies propagation